Pelatihan Pengajaran Pra-Calistung Sebagai Upaya Peningkatan Keterampilan Guru Kb Tk Bintang Nusantara - Eirene Mary; Astrid Maryam Yvonny Nainupu; Ria Ferdika Sitepu; Sri Yulianti (Institut Kristen Teologi Real Batam, 2024)
Early childhood education teaching should be implemented in accordance with the characteristic of early childhood pupils. There are several things to be considered such as learning while playing, understanding of concrete concepts to the abstract and habituation. The implementation of those things will maximize the result of the learning process. These principles also applied in the teaching of reading, writing and mathematics. There is a need for the learning methods that can improve the understanding and the skills of the pupils in those subjects. Teaching methods implemented in Bintang Nusantara Early Child Education School have considered the characteristics of early childhood pupils. Nevertheles, the teachers should be equipped in terms of teaching early reading, early writing and early mathematics. Team from STT Simpson Ungaran held a training program for teaching early reading, early writing and early mathematics to enchance the teaching skills of the Bintang Nusantara Early Childhood Education School teachers. The training conducted using interactive lecture methods and hands-on practice of the methods and activities learned. The teachers gained new knowledge and insights about the teaching reading, writing and mathematics methods for early childhood education. Some of them put into practice of what they have learned in the training.Keywords: Childhood education; pre Reading/Writing/CountingAbstrakPembelajaran untuk PAUD memiliki karakteristik yang sesuai dengan karakter anak PAUD. Ada beberapa hal yang harus diperhatikan dalam melaksanakan pembelajaran PAUD yakni bermain sambil belajar, pemahaman konsep konkrit ke abstrak dan pembiasaan. Penerapan hal tersebut dalam proses pembelajaran akan memaksimalkan hasil pembelajaran. Demikian pula halnya dengan pembelajaran membaca, menulis dan berhitung, perlu memperhatikan hal-hal tersebut. Diperlukan metode pembelajaran yang dapat menunjang pemahaman dan keterampilan calistung untuk anak PAUD. Proses pembelajaran yang dilakukan di KB-TK Bintang Nusantara sudah menerapkan metode pembelajaran yang cocok untuk PAUD. Akan tetapi masih harus terus dilengkapi dalam hal pengajaran pra calistung. Tim pengabdian kepada masyarakat prodi PAK STT Simpson Ungaran mengadakan pelatihan pengajaran pra calistung untuk meningkatkan keterampilan guru-guru KB-TK Bintang Nusantara. Pelatihan dilakukan dengan metode ceramah interaktif dan praktek langsung metode-metode pengajaran pra calistung. Para guru KB-TK Bintang Nusantara mendapatkan wawasan dan pengetahuan baru tentang pola pengajaran pra calistung. Beberapa dari pola tersebut bahkan sudah dipraktekkan dalam kegiatan mengajar.Kata Kunci: Pembelajaran PAUD; pra calistung